The interactions of APC, E-cadherin and beta-catenin in tumour development and progression. - Ilyas, M; Tomlinson, I (1997)
Much progress has been made in identifying genes mutated during the development of colorectal carcinoma. Mutation of the APC gene in particular appears to be fundamental for colorectal tumour initiation. In contrast, loss of expression of E-cadherin appears to be a late event, which may be important in the development of invasion. Recent clarification of the function of APC, however, has shown that it exists in equilibrium with beta-catenin and E-cadherin. This review discusses the function of these molecules, their interactions, and how APC mutations may alter the equilibrium with beta-catenin and E-cadherin. It is argued that these changes cause aberrant architectural development of tissue, which results in loss of growth control. It is this escape from growth control, rather than acquisition of cell-autonomous growth, which results in the initial development of adenomas. The role of the E-cadherin-catenin unit in colorectal tumour invasion is discussed and the evidence is reviewed for the involvement of APC and E-cadherin in tumours arising from non-intestinal epithelia.